Consecuencias jurídicas derivadas del incumplimiento del acuerdo de mediación. Bases para una acción judicial - Gavilanes Verdezoto, Wilson Ramiro (2016)
Legal arising from the implementation and effectiveness of mediation as an alternative mechanism for conflict resolution, which despite the benefits has been perhaps a little helpless in their treatment in the - in this thesis the social problem is observed Ecuador, because the legal text governing procedural life of it was not prepared by the legislature, the consequences that can result from failure of the agreed settlement, legal void that would defenseless who seeks succor of this new procedure of court settlement of conflicts. Based on this guidance, this work meets the objective of investigating the legal consequences of the failure of the mediation agreement in order to warn the need to reform or not Arbitration and Mediation Act. The literature review of conceptual, legal, doctrinaire and the right character compared, allowed me to get a full understanding of the failure of the mediation agreement and its legal consequences. To achieve the results of this study surveys and interviews with legal professionals who develop their activities in the field of mediation were conducted, these results were analyzed using statistical methods, which contributed to the verification of the objectives and testing of the hypothesis. This work is focused on determining an amendment to the Law on Arbitration and Mediation, incorporating an articulated based on the result of the failure of the mediation agreement stipulated in the Act and in particular to impose a penalty arising from such breach.